The Effect of Green Market Orientation, Environmental Awareness, and Innovation on MSME Marketing Performance - Muhammad Galih Wicaksana; Audita Nuvriasari (Arthatama: Journal of Business Management and Accounting, 2025)
The growing emphasis on sustainability has driven Micro, Small, and Medium Enterprises to adopt green business practices, particularly in regions like Yogyakarta with eco-conscious markets. This study aims to analyze the influence of green market orientation, environmental awareness, and green innovation on the marketing performance of green product Micro, Small, and Medium Enterprises in the Special Region of Yogyakarta. A quantitative survey with an associative approach was employed, collecting data from 100 leaders of green Micro, Small, and Medium Enterprises using purposive sampling. The results showed that green market orientation, environmental awareness, and green innovation each have a positive and significant effect on marketing performance, explaining 48.6% of its variability. Green market orientation integrates sustainability into business strategies, environmental awareness reflects attention to ecological impacts, and green innovation fosters eco-friendly product development. These findings suggest that Micro, Small, and Medium Enterprises can enhance sales, market share, and customer satisfaction by prioritizing sustainable practices. The study provides strategic insights for green Micro, Small, and Medium Enterprises to strengthen competitiveness and contributes to the academic understanding of sustainable marketing in localized contexts.